Access to e-books in the libraries of the city of Zagreb - Fabris, Martina (Array, 2008)
The aim of the research has been to show the access to e-books in the libraries of the city of Zagreb (Croatia), either published in physical form in Croatia or abroad. The research was carried out by polling and benchmarking methods in 7 libraries: 4 public libraries from network of Zagreb City Libraries - Bogdan Ogrizović Library, City Library, Medveščak Library, Ravnice Library and 3 libraries of foreign cultural institutes - Goethe Institute Library, Italian Cultural Institute Library and French Institute Library. The acquisition of e-books started as early as 1995 in the City Library. In 4 libraries (57%) e-books are read on site and in 3 libraries (43%) they are lent outside library premises. Annual acquisition ranges from 6 to 30 e-books per library. The hypothesis of the research that e-books in physical form are increasingly acquired and used in the libraries in the city of Zagreb has been confirmed.